2022
DOI: 10.1155/2022/4079524
|View full text |Cite
|
Sign up to set email alerts
|

Developing Machine Learning Techniques to Investigate the Impact of Air Quality Indices on Tadawul Exchange Index

Abstract: The air quality index (AQI) can be described using different pollutant indices. Many investigators study the effect of stock prices and air quality in the field to show if there is a relationship between changing the stock market and the concentration of various pollutants. This study aims to find a relationship between Saudi Tadawul All Share Index (TASI) and multiple pollutants, including particulate matter (PM10), ozone (O3), nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), and AQI. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, various researchers have investigated the effects of international and local events on stock markets, food security indices, and prices. Many events have been considered by these researchers, such as air quality [ 50 ], Ramadan Effects [ 51 ], Syrian Refugee Influx [ 52 ], Crop yield indices [ 5 ], and oil prices [ 53 ]. Table 1 shows several studies that discussed food security issues and several crises that occurred recently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, various researchers have investigated the effects of international and local events on stock markets, food security indices, and prices. Many events have been considered by these researchers, such as air quality [ 50 ], Ramadan Effects [ 51 ], Syrian Refugee Influx [ 52 ], Crop yield indices [ 5 ], and oil prices [ 53 ]. Table 1 shows several studies that discussed food security issues and several crises that occurred recently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that using feature selection will improve the performance of the stock market prediction. On the other hand, Al-Najjar et al (2022c) studied the effect of the air quality index on the stock index movement using machinelearning models. The results indicated an effect between the Saudi stock index movement and PM10, AQI, and O3 pollutants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gulf countries have become an area where many scholars investigate different financial factors [1][2][3]. Along with other countries around the world, Gulf countries are increasingly concerned with food sustainability and crop yield prediction.…”
Section: Introductionmentioning
confidence: 99%